Offprint of Italian Literature: Roots and Branches: Essays in Honor of Thomas Goddard Bergin - Bergin, Thomas Goddard; Rimanelli, Giose; Atchity, Kenneth John (Yale University Press, 1976)
Vena, Michael. Alberti's linguistic innovations.
Keywords: dept.wll; faculty_collection

The Importance of the Spanish Language for North Americans - Méndez-Peñate, Sergio A. (s.n., 1972)
Keywords: Spanish language; United States; dept.wll; faculty_collection

The Spanish and Spanish-American Novel - Méndez-Peñate, Sergio A. (s.n., 1972)
Keywords: History and criticism; History and criticism; Spanish American fiction; Spanish fiction; dept.wll; faculty_collection

Intermediate German. - Werba, Henry (Holt, Rinehart and Winston, 1971)
Keywords: English; German language; Textbooks for foreign speakers; dept.wll; faculty_collection

Marcel Aymé et le Merveilleux. - Dumont, Jean-Louis (Debresse, 1970)
Keywords: Aymé; Marcel; 1902-1967; Marvelous; The; in literature; dept.wll; faculty_collection